2023
DOI: 10.1126/sciadv.adg8304
|View full text |Cite
|
Sign up to set email alerts
|

Why the 2022 Po River drought is the worst in the past two centuries

Alberto Montanari,
Hung Nguyen,
Sara Rubinetti
et al.

Abstract: The causes of recent hydrological droughts and their future evolution under a changing climate are still poorly understood. Banking on a 216-year river flow time series at the Po River outlet, we show that the 2022 hydrological drought is the worst event (30% lower than the second worst, with a six-century return period), part of an increasing trend in severe drought occurrence. The decline in summer river flows (−4.14 cubic meters per second per year), which is more relevant than the precipitation decline, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Previous analysis of long‐term time series of discharge along the Po River pointed out flood peaks in autumn and spring, generated by rainfall and snowmelt events, respectively (Montanari, 2012; Zanchettin et al, 2008), while low discharges are normally observed in February and July (Baruffi et al, 2012), even if changes are expected in the future due to climate change (Montanari et al, 2023; Vezzoli et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis of long‐term time series of discharge along the Po River pointed out flood peaks in autumn and spring, generated by rainfall and snowmelt events, respectively (Montanari, 2012; Zanchettin et al, 2008), while low discharges are normally observed in February and July (Baruffi et al, 2012), even if changes are expected in the future due to climate change (Montanari et al, 2023; Vezzoli et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…On the other part, the 30‐year average rain precipitation in Italy appears to be almost the same as for the entire period, equal to about 970 mm/year, while evapotranspiration has risen by 10 mm/year in Italy in the last 30 years, with a current average of about 490 mm over the entire period. These trends, which are very likely to be associated with global warming, indicate an augmented risk of extreme drought (Montanari et al, 2023), with the consequent land and sandy bars development and vegetation colonization within the channel of the Po River, especially during the summer period.…”
Section: Introductionmentioning
confidence: 99%
“…The latest data from Coldiretti, Italy's main agricultural organization, shows that the extreme event resulted in $ 6 billion in damage to agricultural production (Coldiretti 2022). The 2022 event was not an anomaly, but rather a part of a larger pattern of increasingly frequent and intense droughts in the area (Montanari et al 2023). For the authors, this event could undergo a process of 'mediterranization' of the northern river patterns, where the rivers might become more intermittent, experiencing periods of dryness lasting several months (Levantesi 2022).…”
Section: Study Casementioning
confidence: 99%
“…At the start of 2022, seven months of scarce precipitation led to a reduction in rain and snowmelt, causing a decrease in river flow that was 30% higher than the previous record (Figure 1). This severe and prolonged drought in Northern Italy sparked serious concerns over the socioeconomic impact on agriculture, industry, and energy production [26]. This year was also extremely hot, being the second warmest for Europe and 0.85 • C above the average for the 1991-2020 reference period.…”
Section: Introductionmentioning
confidence: 99%